The Tsar, The Empire, and The Nation Dilemmas of Nationalization in Russia's Western Borderlands, 1905-1915 - Staliūnas, Darius; Aoshima, Yoko (2021)
This collection of essays addresses the challenge of modern nationalism to the tsarist Russian Empire. First appearing on the empire's western periphery, this challenge was most prevalent in twelve provinces extending from Ukrainian lands in the south to the Baltic provinces in the north, and to the Kingdom of Poland. At issue is whether the late Russian Empire entered World War I as a multiethnic state with many of its age-old mechanisms run by a multiethnic elite, or as a Russian state predominantly managed by ethnic Russians. The tsarist vision of prioritizing loyalty among all subjects over privileging ethnic Russians and discriminating against non-Russians faced a fundamental problem: as soon as the opportunity presented itself, non-Russians would increase their demands and become increasingly separatist. The authors found that although the imperial government did not really identify with popular Russian nationalism, it sometimes ended up implementing policies promoted by Russian nationalist proponents. Matters addressed include native language education, interconfessional rivalry, the "Jewish question," the origins of mass tourism in the western provinces, and the emergence of Russian nationalist attitudes in the aftermath of the first Russian revolution.